Prosedur Penjualan Jasa Kamar Guest House Pada CV. Sintesa Kreasi Bersama di Surabaya - Risda Vera Fitria; Tjandra Wasesa; Diana Zuhro; Sutini Sutini; Heri Toni; Wiratna Wiratna (Universitas 45 Surabaya, 2023)
In 2023, many economic actors will carry out business activities and compete fiercely among other business actors, both those operating in the industrial, trade and service sectors. However, in general, companies are founded by business actors to achieve predetermined goals such as current economic conditions. So the company will carry out strategies such as accounting information systems which are useful for improving the effectiveness and quality of work. Starting from a trading company where the company has the main activity of buying goods from suppliers and reselling them to consumers with physical changes or not. Meanwhile, service companies are companies whose main activity is providing various services such as convenience, security, and so on. Service companies consist of various kinds, an example of one of which is a hotel service company, hotels themselves also come in various forms such as hotels, inns, guest houses, dormitories, apartments and villas. A hotel is a building provided for people to stay overnight or take a break in the hope of getting services and other facilities for a fee, including other buildings that are integrated, managed by the same party, except for shops and offices (Government Regulation of the Republic of Indonesia Number 65 of 2001 dated 31 September 2001 article 1) (Wiyasha, Hospitality Accounting - Uniform Application System of Accounts Lodging Industry, 2010).